Magnetic Fields in the Solar System Planets, Moons and Solar Wind Interactions (Astrophysics and Space Science Library,, 2018)
This book addresses and reviews many of the still little understood questions related to the processes underlying planetary magnetic fields and their interaction with the solar wind. With focus on research carried out within the German Priority Program "PlanetMag", it also provides an overview of the most recent research in the field. Magnetic fields play an important role in making a planet habitable by protecting the environment from the solar wind. Without the geomagnetic field, for example, life on Earth as we know it would not be possible. And results from recent space missions to Mars and Venus strongly indicate that planetary magnetic fields play a vital role in preventing atmospheric erosion by the solar wind. However, very little is known about the underlying interaction between the solar wind and a planet's magnetic field. The book takes a synergistic interdisciplinary approach that combines newly developed tools for data acquisition and analysis, computer simulations of planetary interiors and dynamos, models of solar wind interaction, measurement of ancient terrestrial rocks and meteorites, and laboratory investigations.